2000
DOI: 10.1002/1097-4636(200010)52:1<164::aid-jbm21>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

A novel injectable bioactive bone cement for spinal surgery: A developmental and preclinical study

Abstract: The injection of bone cement by minimally invasive techniques for the treatment of vertebral body fractures or for stabilization of an osteoporotic vertebral body is regarded as promising in spinal surgery. The purpose of this study was to develop a novel injectable bioactive bone cement to address such concerns. The cement was composed mainly of strontium-containing hydroxyapatite (Sr-HA) filler and Bisphenol A Diglycidylether Dimethacrylate (D-GMA) resin. The Sr-HA filler was prepared by precipitation and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…However, PMMA sets by a polymerization of toxic monomers, which also evolves significant amounts of heat that damages tissues. Moreover, it is neither degradable nor bioactive, it does not bond chemically to bones and might generate particulate debris leading to an inflammatory foreign body response [104,110]. A number of other non-degradable polymers applied in orthopedic surgery include PE in its different modifications such as low density PE, high-density polyethylene (HDPE), and Ultrahigh molecular weight polyethylene (used as the articular surface of total hip replacement implants [111,112]), polyethylene terepthalate, polypropylene, and PTFE, which are applied to repair knee ligaments [113].…”
Section: Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PMMA sets by a polymerization of toxic monomers, which also evolves significant amounts of heat that damages tissues. Moreover, it is neither degradable nor bioactive, it does not bond chemically to bones and might generate particulate debris leading to an inflammatory foreign body response [104,110]. A number of other non-degradable polymers applied in orthopedic surgery include PE in its different modifications such as low density PE, high-density polyethylene (HDPE), and Ultrahigh molecular weight polyethylene (used as the articular surface of total hip replacement implants [111,112]), polyethylene terepthalate, polypropylene, and PTFE, which are applied to repair knee ligaments [113].…”
Section: Polymersmentioning
confidence: 99%
“…As a result, quick setting and degradable biocomposite cements with a low-heat output and compressive strengths in the range of 1 to 12 MPa were prepared by varying the molecular weight of PPF, as well as the contents of the monomer, b-TCP, initiator, and porogen (NaCl) [453,454]. An acrylic cement with Sr-containing HA as a filler [110] and an injectable polydimethylsiloxane/HA cement [455] have been prepared as well.…”
Section: Calcium Orthophosphate Cement-based Biocomposites and Concretesmentioning
confidence: 99%
“…6 In spite of the success claimed for PVP and the growing interest for this technique, there are only a few literature reports of studies dealing with injectable and radiopaque acrylic bone cement specially designed for this purpose. 7 Li et al 7 reported excellent radiopacity and injectability of an acrylic bone cement containing strontium hydroxyapatite as the radiopaque agent.…”
Section: Introductionmentioning
confidence: 99%
“…To be suitable for use in bone defect repair, a bone cement should not only have the characteristics of rapid setting but also adequate stiffness, which confers immediate load-bearing capacity and stiffness resembling the natural bone more closely (Li et al 2000;Burguera et al 2006). Moreover, high early strength is needed to prevent early-stage implant failure or disintegration (Dorozhkin 2008).…”
mentioning
confidence: 99%